Lifestyle Intervention for Prevention of Type 2 Diabetes in Primary Health Care: One-year follow-up of the Finnish National Diabetes Prevention Program (FIN-D2D) - Saaristo, Timo; Moilanen, Leena; Korpi-Hyövälti, Eeva; Vanhala, Mauno; Saltevo, Juha; Niskanen, Leo; Jokelainen, Jari; Peltonen, Markku; Oksa, Heikki; Tuomilehto, Jaakko; Uusitupa, Matti; Keinänen-Kiukaanniemi, Sirkka (Diabetes care, 2010)
OBJECTIVE: To investigate 1-year outcomes of a national diabetes prevention program in Finland. RESEARCH DESIGN AND METHODS: Altogether 10,149 individuals at high risk for diabetes were identified with the Finnish Diabetes Risk Score (FINDRISC; scoring ≥15 points), by a history of impaired fasting glucose (IFG) or impaired glucose tolerance (IGT), cardiovascular disease, or gestational diabetes mellitus in 400 primary health care centers. One-year follow-up data were available for 2,798 participants who were nondiabetic at baseline (919 men and 1,879 women, aged 56.0 ± 9.9 and 54.0 ± 10.7 years [mean ± SD] with BMI 30.9 ± 4.6 and 31.6 ± 5.4 kg/m²). RESULTS: The incidence of diabetes was 2.0 and 1.2% in men and women with normal glucose tolerance at baseline, 13.5 and 7.4% in those with IFG, and 16.1 and 11.3% in those with IGT, respectively. Altogether 17.5% of the subjects lost ≥5% weight with no sex difference. The relative risk of diabetes was 0.31 (95% CI 0.16-0.59) in the group who lost ≥5% weight, 0.72 (0.46-1.13) in the group who lost 2.5-4.9% weight, and 1.10 (0.77-1.58) in the group who gained ≥2.5% compared with the group who maintained weight. CONCLUSIONS: The FIN-D2D was the first national effort to implement the prevention of diabetes in a primary health care setting. Methods for recruiting high-risk subjects were simple and easy to use. Moderate weight loss in this very high-risk group was especially effective in reducing risk of diabetes among those participating in the program.